THE LORD OF UKRAINIAN STUDENTS’ MINDS: TO THE PROB-LEM “IVAN FRANKO AND NATIONAL SPIRITUAL ORIEN-TATION OF STUDENTS’ YOUTH OF BUKOVYNA (1880-1916)” - Мakarovskiy I. P. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article is dedicated to the exploration of the role of Ivan Franko as a writer and thinker in forming of national spiritual orientation of students’ youth of his time.